Pengembangan Instrumen Kemampuan Pemecahan Masalah Matematika Peserta Didik Di SMA - Talib Idrus; Sarson W. Pomalato; Sumarno Ismail; Abdul D. Mohidin (Department of Mathematics, Universitas Negeri Gorontalo, 2023)
When a teacher conducts an assessment of the ability of students to solve problems, a good test instrument is needed. However, in reality there are still many teachers who use test instrument without going through an expert assessment process, causing the assessment of student learning outcomes to be less than optimal. The purpose of this study was to produce a test instrument for high school students' mathematical problem solving abilities. The type of research used was Research and Development (RD). The sample used was students of SMA N 1 TAPA class XI IPA with a total of 100 people. The Thiagarajan, Semmel, and Semmel (4D) development model was used in this research. The research was divided into 3 stages of the development procedure (preliminary study stage, development stage, and testing stage). The results of the study show that the resulting instrument is valid, with CVR and CVI = 1 and has a high level of reliability (0.77). Based on the results of the implementation of the test instrument in the field trial class, it showed that the assessment of student learning outcomes was more optimal, which was obtained if students' mathematical solving abilities were quite optimal even though there were still indicators that were included in the less category. By developing this test instrument, it will optimize teacher assessment in assessing student learning outcomes, especially in solving math problems.